Morphophysiological and Vanillin Quality Evaluation of Vanilla Plants (Vanilla planifolia Andr.) under Water Stress - Avianto, Yovi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Vanilla (Vanilla planifolia Andr.) is a globally popular flavoring cultivated in tropical regions such as Madagascar, Indonesia, and Mexico. Due to global climate change, particularly the El Niño phenomenon, droughts have become more frequent, impacting water availability and quality for vanilla plants. This study addresses these challenges by examining the plant’s responses to drought at a vanilla plantation in Yogyakarta, Indonesia, over two years. A completely randomized design was used, testing five water stress levels (100%, 50%, 25%, 150%, and 200% field capacity). Variables measured included relative water content, physiological activity, chlorophyll, proline content, leaf total acid, photosynthesis efficiency, and morphological traits. Data analysis was performed using ANOVA and Tukey’s HSD test. Vanilla plants exhibited significant physiological and morphological changes in response to varying water conditions. Severe drought (25% water stress) led to reduced relative water content, chlorophyll levels, and CO₂ assimilation, alongside increased proline accumulation. Moderate drought (50% water stress) had a lesser impact. Under field capacity (100%) and excess water (150% and 200%), plants maintained higher relative water content and chlorophyll levels, efficient CO₂ assimilation, and optimal morphological traits. The presence of proline under excess water suggests a dual stress response to drought and waterlogging. Beans from severely drought-stressed plants showed a significant decrease in vanillin content and weight. Identifying and developing vanilla varieties with greater tolerance to water scarcity is essential to ensure sustainable production in the face of climate change.